Recombinant IL-1Ra Stimulation of Native NP Cells Inhibits a Multitude of Pathological Features. (May 2014) - Daniels, J.; Binch, A. LA.; Chiverton, N.; Cole, A.; Michael, A. R.; Breakwell, L.; Le Maitre, C. L.
Introduction: Interleukin-1 (IL-1) has been implicated in the pathogenesis of disc degeneration, with increased levels seen during degeneration without a concordant increase in its natural inhibitor: IL-1 receptor antagonist (IL-1Ra). IL-1 has been shown to stimulate a pleathora of catabolic actions including matrix degrading enzymes, cytokines, chemokines, and factors which promote nerve and blood vessel ingrowth. Here, we investigated the effect of the natural inhibitor of IL-1, to determine its ability to inhibit catabolic events regulated by natively produced IL-1 in degenerate human nucleus pulposus (NP) cells. Materials and Methods: Human NP cells were isolated via collagenase digestion from four human intervertebral disc (IVD) obtained from degenerate disc samples from patients undergoing discetomy. Following expansion in monolayer culture, cells were transferred to alginate bead cultures at passage two and maintained for 2 weeks before stimulation with IL-1Ra to enable redifferentiation to take place. Cells were treated with IL-1Ra at 1, 10, 100 pg/mL and 1, 10, 100 ng/mL for 48 hours. Following stimulation, cells were released from alginate beads and RNA isolated using Trizol reagent. cDNA synthesized and real-time PCR used to determine the effects on a wide range of gene targets including matrix metalloproteases (MMPs), cytokines, chemokines, and factors involved in nerve ingrowth (NGF), pain pathways (substance P), and angiogenesis (vascular endothelial growth factor, VEGF). Results: Baseline levels of all factors investigated varied between patients as did the overall responsiveness to IL-1Ra stimulation. IL-1Ra stimulation resulted in decreased gene expression for several MMPs including MMPs 3 and 13; cytokines including IL-1 and IL-6; chemokines including IL-8, CCL2, and CXCL3. NGF, substance P, and VEGF were also all decreased by IL-1Ra stimulation. Effective doses were target and patient-specific and while the highest dose of IL-1Ra often resulted in decreased expression of catabolic factors in all patients, lowest doses (1.10 pg/mL IL-1Ra) resulted in stimulation of some catabolic responses in some patients, for example, IL-6 and IL-8 were increased in two out of four patient samples investigated at low doses of IL-1Ra. Conclusion: IL-1 has been implicated as a key factor in the pathogenesis of disc degeneration, however till date it is not fully understood whether inhibition of this cytokine in native disc cells can inhibit the plethora of pathogenic factors linked to IL-1. This study has demonstrated that treatment of NP cells with IL-1Ra results in decreased expression of MMPs, cytokines, chemokines, nerve, and blood vessel growth factors and neurotrophic factors, suggesting IL-1Ra could be a useful agent in the prevention of further degeneration to create the correct tissue niche to support tissue regeneration. However, patient responses were seen to be variable, with some patients displaying increased expression of some catabolic factors at low doses of IL-1Ra, thus selection of patients and carefully controlled drug release would be essential to enable such a therapy to be deployed successfully. Disclosure of Interest None declared